Affinity Chromatography of Human Factor VIII Using Human and Rabbit Antibodies to Factor VIII - Lane, Janet L; Ekert, H; Vafiadis, A (Thrombosis and Haemostasis, 1979)
Factor VIII, purified by gel filtration on Sepharose 2B, has an 8 band multiple subunit structure, with molecular weights ranging from 30,000 to 230,000, on reduction and SDS-PAGE at a protein concentration of 400 μg/gel. Affinity chromatography of this factor VIII preparation with insolubilized haemophilic antibody to factor VIII showed that 45-81% VIII:C and 0-33% VIILRag were attached to the column. Elution of the column with 0.25 M CaCl2 did not show VIII:C or VIILRag in the eluate. NH4SCN dissociation of the column, followed by reduction and SDS-PAGE of the dissociated protein, showed that 95 % of the protein bound by haemophilic antibody had a molecular weight similar to the low molecular weight subunits of the reduced factor VIII.In control experiments with normal Human IgG, 3% of VIII:C and 5% of VIILRag were attached to the column. NH4SCN dissociation of the column, followed by reduction and SDS-PAGE of the protein, showed 2 faint bands with molecular weight consistent with heavy and light chains of IgG.Similar experiments with antibody to factor VIII showed that 67-83% of VIILC and 61-76% of VIII:Rag were attached to the column. Elution of the column with 0.25 M CaCl2 showed 10% of the applied VIII:C, but no VIII:Rag in the eluate. NH4SCN dissociation of the column, followed by reduction and SDS-PAGE of the dissociated protein, showed an 8 band subunit structure similar to the reduced factor VIII.